The Prognostic Value of ANGPTL-4 in Acute Coronary Syndrome: A Prospective Cohort Study - Luxitaa Goenka; Ritwika Sinha Ray; Vengatesh Munnusamy; VE Dhandapani; Melvin George (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Coronary Artery Disease (CAD) is one of the leading causes of mortality and morbidity worldwide and Acute Coronary Syndrome (ACS) is one of the predominant causes of Cardiovascular Deaths (CVD). Aim: To determine if Angiopoietin-like Protein-4 (ANGPTL-4) might be a potential predictor of Major Adverse Cardiac Events (MACE) in ACS patients. Materials and Methods: This prospective cohort study was conducted in the Department of Cardiology and Clinical Pharmacology, SRM MCH and RC, Kattankulathur, between January 2016 and March 2018. Authors measured serum ANGPTL-4 at admission in 120 ACS patients using Enzymelinked Immunosorbent Assay (ELISA) with a commercially available (Ray Biotech Human ANGPTL-4 ELISA, GA, USA) kit. The patients were followed up through a telephonic interview to record MACE. Independent Samples t-test and chi-square test were used to compare the differences in the continuous and categorical data, between the groups respectively. Receiver Operating Curve (ROC) was plotted to predict the ability of ANGPTL-4 to predict MACE among ACS patients. Kaplan-Meier survival analysis was performed and the survival rate between those with high and low ANGPTL-4 levels was compared using the log-rank test. All statistical analyses were performed with SPSS version 16.0 (SPSS Inc., Chicago, IL). All p-values<0.05 were considered statistically significant. Results: A total of 120 ACS patients were included for the study. During the median follow-up of 24 (22-25.75) months, MACE had occurred among 14 patients. Ten patients were lost to follow-up. Kaplan Meier survival curve was plotted for patients with low and high ANGPTL-4 levels and the log-rank test failed to show a significant difference in the survival rate between the two groups (χ2 =0.100, p=0.75). ANGPTL-4 failed to show any significant difference in the survival rate in both diabetic (χ2 =0.002, p=0.97) and hypertensive (χ2 =0.002, p=0.96) ACS patients. Conclusion: In conclusion, the present study data failed to demonstrate that ANGPTL-4 could be a potential biomarker for the prediction of MACE among ACS patients. However, larger studies are warranted to investigate the prognostic value of ANGPTL-4 among ACS patients.